Overview Of Passenger Service Standards Above Kmp. Siginjai Lintas Jepara – Karimunjawa Based On Pm 62 Year 2019 In Central Java Province - Purboyo Purboyo; Monica Amanda; Inayatul Fatikhah (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2022)
Central Java Province is located at 5°40' – 8°30' South Latitude and 108°30' – 111°30' East Longitude. The area reaches 32,548 km² or 25.67 percent of the land area of Java-Madura. The furthest distance from west to east is 263 kilometers and from north to south 226 kilometers (excluding Karimunjawa island). Central Java is bordered by the Indian Ocean and DI Yogyakarta in the south, West Java Province in the west, East Java Province in the east, and the Java Sea in the north. The province of Central Java also includes Nusakambangan Island in the south, and the Karimunjawa Islands in the Java Sea. In order to create services that are in accordance with the level of passenger service, analysis is neededusing the method of conformity level of minimum service standards for passengers with existing conditions. Based on this analysis, it can be concluded that there are variables that are still lacking in the services of several ferry transportations such as:Information and Safety Facilities that are easily visible and affordable are not yet available in the form of health workers, stretchers, and inadequate first aid kits, the absence of passenger service facilities, not yet available proper temperature control facilities, passenger toilet facilities according to needs, no breastfeeding mother room facilities, no wheelchair special room facilities and special room facilities for wheelchair users